UPAYA PENINGKATAN KEMAMPUAN PENGELOLAAN KECEMASAN PADA IBU HAMIL DALAM KEGIATAN SENAM DI KLINIK BERSALIN KURNIA KEC.MEDAN DENAI, KOTA MEDAN - Megawati Sinambela; Rostio Girsang; Herri Novita (INSTITUT KESEHATAN DELI HUSADA, 2021)
Pregnancy is a period that starts from conception until the birth of the fetus (Widatiningsih 2017). Meanwhile, according to Dahro (2012) pregnancy is defined as a period where there are dramatic changes in both physiological, psychological and adaptation in women. Pregnancy and the puerperium can sometimes lead to psychosis. Anxiety is a state of unpleasant affective feelings accompanied by physical sensations that alert people to impending dangers. Based on the study of Gourount, et al with 133 study subjects pregnant women with gestational age 9-37 weeks showed that anxiety occurs 50% in the first trimester, 71.4% in the second trimester and 80% in the third trimester. Yoga is a combination of body, mind and mental exercises that really help pregnant women flex their joints and calm the mind, especially in the third trimester. Yoga yoga exercises have five aspects, namely physical yoga practice, breathing (pranayama), positions (mudra), meditation and deep relaxation which can be used to get benefits during pregnancy that can help smooth pregnancy and childbirth naturally and healthy (Rusmita, El , 2015). Prenatal yoga has a positive effect on pregnant women, namely reducing stress, anxiety, pain during pregnancy, discomfort and reducing labor pain. Sindhu also stated that one of the benefits of practicing yoga for pregnancy is that it reduces anxiety and mentally prepares the mother for childbirth. According to research by Kyle Davis, et al, which involved 46 pregnant women with symptoms of anxiety, showed that prenatal yoga was a feasible and acceptable intervention for pregnant women who had symptoms of anxiety and depression. Participants also expressed high satisfaction and there were no adverse results (Kemens RI, 2016).